2017
DOI: 10.1094/pdis-08-16-1129-re
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Molecular Properties of aTurnip mosaic virus(TuMV) Strain that Breaks TuMV Resistances inBrassica napus

Abstract: A new resistance-breaking strain of Turnip mosaic virus (TuMV) overcomes TuMV resistance genes that currently suppress spread of this virus in Brassica napus crops in the Liverpool Plains region of eastern Australia. Isolates 12.1 and 12.5 of this strain and three other isolates in TuMV pathotypes 1 (NSW-2), 7 (NSW-1), and 8 (WA-Ap1) were inoculated to plants of 19 B. napus cultivars and one breeding line. All plants of these cultivars and the breeding line proved susceptible to 12.1 and 12.5 but developed onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 41 publications
2
29
0
7
Order By: Relevance
“…Despite the importance of TUMV and its negative effect to the production of many crops, mainly the studies focusing on Brassicaceae were reported [ 28 , 29 , 30 , 31 , 32 ]. On the contrary, there is no data about the TuMV/oilseed poppy relationship [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the importance of TUMV and its negative effect to the production of many crops, mainly the studies focusing on Brassicaceae were reported [ 28 , 29 , 30 , 31 , 32 ]. On the contrary, there is no data about the TuMV/oilseed poppy relationship [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…showed segregating systemic resistance and extreme resistance (Nyalugwe et al, 2015a). Guerret et al (2017) examined responses to five isolates of TuMV (one each in pathotypes 1, 7, and 8, and two unpathotyped isolates) against one cultivar of each of three subspecies of B. oleracea, with the following results: (1) cauliflower was extremely resistant to all of the isolates;…”
Section: B Nigramentioning
confidence: 99%
“…(2) cabbage showed extreme resistance to pathotype 8, segregating extreme resistance and systemic resistance with symptomless local infection to pathotypes 1 and 7, and segregating extreme resistance and systemic infection with the two unpathotyped isolates: and (3) broccoli showed extreme resistance to pathotypes 1 and 7, local symptoms and systemic resistance to pathotype 8, and susceptibility to the unpathotyped isolates (Guerret et al, 2017).…”
Section: B Nigramentioning
confidence: 99%
“…In Australia, blackleg and sclerotinia have been identified as the most destructive diseases for oilseed-and vegetable-type mustards (Murray and Brennan, 2012;Uloth et al, 2013Uloth et al, , 2014Uloth et al, , 2015aUloth et al, , 2015bVan de Wouw et al, 2016). However, there are several other diseases also identified as important in Australia, including TYV, downy mildew, white leaf spot, alternaria blight, bacterial leaf blight, and powdery mildew (Li et al, 2006a(Li et al, , 2007(Li et al, , 2008a(Li et al, , 2009bEshraghi et al, 2007;Murray and Brennan, 2012;Gunasinghe et al, 2014;Van de Wouw et al, 2016;Mohammed et al, 2017Mohammed et al, , 2018aMohammed et al, , 2018bMohammed et al, , 2019Al-lami et al, 2019aAl-lami et al, , 2019bAl-lami et al, , 2019cGuerret et al, 2017;Uloth et al, 2016Uloth et al, , 2018Murtza et al, 2019).…”
Section: Is E a S E S Affec Ting B Junce Amentioning
confidence: 99%
“…Several TuMV resistance phenotypes and/or single gene resistances are found in B. napus and B. carinata Jenner, 2002, 2006;Nyalugwe et al, 2014). However, a strain of TuMV that overcame all TuMV resistance genes in B. napus, failed to overcome dominant TuMV hypersensitive resistance gene TuRBJU01, found in B. juncea (Nyalugwe et al, 2016a(Nyalugwe et al, , 2016b(Nyalugwe et al, , 2016cGuerret et al, 2017). TuRBJU01 was identified by studying Mendelian segregation in a population arising from a cross that included TuMV-resistant B. juncea 'Oasis CL' as a parent (Nyalugwe et al, 2015a(Nyalugwe et al, , 2016a.…”
Section: Viral Diseasesmentioning
confidence: 99%